Effect of organizational culture and quality management on innovation among Nigerian manufacturing companies: The mediating role of dynamic capabilities. Issue 4 (2nd October 2021) - Shuaib, Kabir Musa; He, Zhen; Song, Lisha
Abstract: Organizations are becoming more interested in establishing a unique organizational culture capable of implementing changes to achieve common goals. Research on organizational culture and quality management and how it drives innovation is essential in understanding how individuals and groups support implementing programs and activities to achieve organizational goals sustainably. The paper, therefore, examines the mediating role of dynamic capabilities on the relationship between organizational culture, quality management, and innovation among Nigerian manufacturing companies. The study collected empirical data from 400 manufacturing companies registered with the manufacturers association of Nigeria that implements quality management models using a convenience sampling technique. A partial least square model was used for data analysis. The result reveals that all the organizational culture dimensions and quality management practices are positively and significantly related to innovation. Furthermore, the results show that dynamic capabilities played a positive and significant mediating role between organizational culture, quality management practices, and innovation. However, the relationship between dynamic capabilities and innovation was found to be positive but insignificant. In contrast, a positive and significant relationship was revealed between all the individual dimensions (sensing, learning, integrating, and coordinating) capabilities and innovation among Nigerian manufacturing firms. Thus, the study contributes to a better understanding of how manufacturing companies combine quality management practices and organizational culture to improve innovation through dynamic capabilities with empirical evidence.